The influence of maximum strength performance in seated calf raises on counter movement jump and squat jump in elite junior basketball players - Warneke, K.; Keiner, M.; Lohmann, L. H.; Hillebrecht, M.; Wirth, K.; Schiemann, S. (SportMont, 2022)
In basketball high intensity jumping and sprinting performance is of high importance. There seems to be a relationship between maximal strength (MSt) and jumping performance in general, but influence of MSt in the plantar flexors and jumping performance seems not to be investigated very well. Thus, the aim of this study was to investigate the influence of MSt in the plantar flexors on jumping performance. 37 young elite basketball players were included (age: 13.9±1.8 years; weight: 66.4±16.8 kg; height: 179.21±13.24 cm) and countermovement jump (CMJ) and squat jump (SJ) height as well as unilateral and bilateral maximal isometric contraction in the plantar flexors with bended knee joint were assessed. Pearson correlations were calculated for MSt and jumping performance and Bland-Altman Analysis was performed to determine the level of variance between bilateral MSt assessment and cumulated MSt value of unilateral measurements. This study shows a moderate influence of isometric MSt in the calf muscle on jumping performance, so it seems beneficial to include the training of the plantar flexors in the training routine of basketball players. When determining MSt, the bilateral force deficit must be considered, even though there was no influence on determined correlations.